Chemically modified aptamers for improving binding affinity to the target proteins via enhanced non-covalent bonding - Chen, Zefeng; Luo, Hang; Gubu, Amu; Yu, Sifan; Zhang, Huarui; Dai, Hong; Zhang, Yihao; Zhang, Baoting; Ma, Yuan; Lu, Aiping; Zhang, Ge (Frontiers in Cell and Developmental Biology, 2023)
Nucleic acid aptamers are ssDNA or ssRNA fragments that specifically recognize targets. However, the pharmacodynamic properties of natural aptamers consisting of 4 naturally occurring nucleosides (A, G, C, T/U) are generally restricted for inferior binding affinity than the cognate antibodies. The development of high-affinity modification strategies has attracted extensive attention in aptamer applications. Chemically modified aptamers with stable three-dimensional shapes can tightly interact with the target proteins via enhanced non-covalent bonding, possibly resulting in hundreds of affinity enhancements. This review overviewed high-affinity modification strategies used in aptamers, including nucleobase modifications, fluorine modifications (2'-fluoro nucleic acid, 2'-fluoro arabino nucleic acid, 2',2'-difluoro nucleic acid), structural alteration modifications (locked nucleic acid, unlocked nucleic acid), phosphate modifications (phosphorothioates, phosphorodithioates), and extended alphabets. The review emphasized how these high-affinity modifications function in effect as the interactions with target proteins, thereby refining the pharmacodynamic properties of aptamers.